A novel cool material: ASA (acrylonitrile-styrene-acrylate) matrix composites with solar reflective inorganic particles. (16th June 2017) - Xiang, Bo; Yin, Xiuping; Zhang, Jun
Abstract: Nowadays, the undesirable heat generated from solar energy troubles people a lot in various aspects, including the energy consumption for cooling purposes, the potential safety hazards of the outdoor devices used in high-temperature environment and so on. Therefore, many cool materials emerge as the times require, which can mitigate these serious situation. In this study, a concept of solar reflective ASA (acrylonitrile-styrene-acrylate terpolymer) for cool material was proposed. To achieve this purpose, several inorganic particles with high solar reflectance were chosen to mix with ASA via melt blending to improve the cooling property of ASA. Ultraviolet-visible-near infrared (UV-Vis-NIR) spectral and temperature test were carried out to evaluate the cooling properties of ASA and its hybrid composites. The results of the solar spectral test showed that the addition of only 1% volume fraction of inorganic particles could effectively improve the solar reflectance of ASA. And ASA/barium titanate (BaTiO3 ) hybrid composite possessed the highest reflectance value of 67.66%, nearly 2 times that of neat ASA. The results of the indoor temperature test were in highly consistent with those of the solar reflectance, which showed that all the hybrid composites presented better cooling effect compared with neat ASA. Also, ASA/BaTiO3 hybrid composite exhibited the best cooling effect, nearly 10 °C lower than neat ASA. Besides, the outdoor temperature test showed the same trend with the indoor temperature test. Furthermore, the results of the mechanic test indicated that the improvement of the cooling properties was based on no sacrifice of the mechanical properties.